Analysis of Semiotics of the Anakkon Hi Do Hamoraon Di Au Philosophy in Marparbue Do Lojami Lyrics (Study of Parental Sacrifice and Loving Parents (Mother) - Sagala, Rotama Enjel; Ginting, Lokasita Primadona; Harahap, Muharrina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research contains the Philosophical Semiotics Analysis of the Lyrics of Anakkon Hi Do Hamoraon Di Au in Marparbue Do Lojami's Song Lyrics. The data collection technique in this study is library research, namely by recording all data related to the problems studied with various librarian documents, such as books, articles, and manuscripts published in newspapers, magazines, and the internet. This study shows how songs become a medium used to represent the cultural identity of a society. The community referred to in this study is the Toba Batak community. Batak Toba, one of the tribes in Indonesia, comes from the island of Sumatra, namely North Sumatra. The socio-cultural system of the Toba Batak society plays an important role in creating a harmonious culture, especially in the sustainability of children's education in the Toba Batak family. Generally, Toba Batak people everywhere have the philosophy of "anakkon hi do Cameroon di au". It means that my son is my treasure. Because almost most of the active roles of Toba Batak parents in sending their children to school seem so thick, they are willing to fight hard for the success of their children.